Geochronology and geochemistry of the Late Jurassic-Early Cretaceous Sangxiu Formation volcanic rocks of the Chegu region, Southern Tibet - Wu, Feng; Wang, Lixin; Huo, Zhitao; Liao, Jia; Tang, Yao; Yang, Tao; Li, Xin; Wang, Shijie; Xiao, Hongji; Cao, Binhua (Frontiers in Earth Science, 2023)
The evolution patterns of the Neo-Tethys Himalayas have been a major topic of research, particularly in the Neo-Tethys Ocean. The geological field investigations were conducted in the Late Jurassic-Early Cretaceous Sangxiu Formation in the Tsomei Longzi area of Tibet. A stratigraphic hierarchy of the Sangxiu Formation was established based on an analysis of the sedimentary lithology in this area. Based on the geochemical characteristics and chronology of the felsic-mafic volcanic rocks of the Sangxiu Formation, the genesis, tectonic background, and evolutionary pattern of the volcanic rocks of the Sangxiu Formation were revealed. Basalts, dolerite, and volcanic debris constitute the volcanic rocks of the Sangxiu Group in the Zhegu area. The Early Cretaceous Sangxiu Formation basalts were determined using SHRIMP zircon U-Pb ages of 141 ± 1 Ma and 142 ± 1 Ma. Volcanic rocks of the Sangxiu Formation, which are intraplate rifting products of the Late Jurassic-Early Cretaceous period, originated from the mantle and mixed with crustal materials. The rock type is an intraplate alkaline basalt that formed during the rifting activity of the passive continental margin extension. There was a crucial growth episode in the Neo-Tethys Ocean during the Late Jurassic and Early Cretaceous. The Neo-Tethys Ocean expansion from the Late Triassic to the Early Cretaceous was caused by a younger rifting along the passive continental edge rather than a continuation of the early Mid-Ocean Ridge development, thus demonstrating the expansion of the Neo-Tethys Ocean at various stages.